Dosimetric predictors of toxicity and quality of life following prostate stereotactic ablative radiotherapy. (March 2020) - Alayed, Yasir; Davidson, Melanie; Quon, Harvey; Cheung, Patrick; Chu, William; Chung, Hans T.; Vesprini, Danny; Ong, Aldrich; Chowdhury, Amit; Liu, Stanley K.; Panjwani, Dilip; Helou, Joelle; et al.
Highlights: We report the dosimetric predictors of late toxicity and QOL in prostate SABR. 258 patients with a median follow up of 6.1 years from 4 phase II trials. For QOL, bladder V38 was significant on multivariate analysis. For late toxicity, rectal Dmax, rectal V38 and bladder D2cc were significant. Caution must be taken to avoid hotspots in the bladder and rectum. Abstract: Purpose: SABR offers an effective treatment option for clinically localized prostate cancer. Here we report the dosimetric predictors of late toxicity and quality of life (QOL) in a pooled cohort of patients from four phase II trials. Methods: The combined cohort included all three prostate cancer risk groups. The prescription dose was 35–40 Gy in 5 fractions. Toxicity (CTCAE) and QOL (EPIC) were collected. Multiple dosimetric parameters for the bladder, rectum and penile bulb were collected. Univariate (UVA) followed by multivariate (MVA) logistic regression analysis was conducted to search for significant dosimetric predictors of late GI/GU toxicity, or minimal clinically important change in the relevant QOL domain. Results: 258 patients were included with median follow up of 6.1 years. For QOL, bladder Dmax, V38, D1cc, D2cc, D5cc and rectal V35 were predictors of urinary and bowel MCIC on UVA. On MVA, only bladder V38 remained significant. For late toxicity, various parameters were significant on UVA but only rectal Dmax, V38 and bladder D2cc were significant predictors on MVA. Conclusions: This report confirms that the high-dose regions in the bladder and rectum are more significant predictors of late toxicity and QOL after prostate SABR compared to low-dose regions. Caution must be taken to avoid high doses and hotspots in those organs.